2004
DOI: 10.1158/0008-5472.can-04-2727
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel and Specific Inhibitor of the Ataxia-Telangiectasia Mutated Kinase ATM

Abstract: The serine/threonine protein kinase ATM signals to cell cycle and DNA repair components by phosphorylating downstream targets such as p53, CHK2, NBS1, and BRCA1. Mutation of ATM occurs in the human autosomal recessive disorder ataxia-telangiectasia, which is characterized by hypersensitivity to ionizing radiation and a failure of cells to arrest the cell cycle after the induction of DNA double-strand breaks. It has thus been proposed that ATM inhibition would cause cellular radio-and chemosensitization. Throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
961
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,108 publications
(1,010 citation statements)
references
References 48 publications
45
961
1
3
Order By: Relevance
“…The ATM kinase inhibitor KU55933 (Hickson et al, 2004) inhibited ATM activation and this protein was not detected at the site of cleavage, but as expected Nbs1 still localized to the break, since this is ATM-independent. Furthermore, while ectopically expressed ATM localized to I-Ppo1 DSB in A-T cells, neither a kinase dead nor an S1981A mutant form of ATM bound to the DSB.…”
Section: Viral Infection and In Vitro Models To Investigate The Rolesupporting
confidence: 56%
“…The ATM kinase inhibitor KU55933 (Hickson et al, 2004) inhibited ATM activation and this protein was not detected at the site of cleavage, but as expected Nbs1 still localized to the break, since this is ATM-independent. Furthermore, while ectopically expressed ATM localized to I-Ppo1 DSB in A-T cells, neither a kinase dead nor an S1981A mutant form of ATM bound to the DSB.…”
Section: Viral Infection and In Vitro Models To Investigate The Rolesupporting
confidence: 56%
“…Since ATM showed the relatively early activation following thymidine treatment in the presence or absence of Chk1 inhibitor, the effect of ATM inhibition on immortalized normal urothelial cells during DNA replication stress was then examined. hTERT-NHU cells were firstly treated with 10 M of the highly specific ATM inhibitor KU55933 (Hickson et al, 2004) for 2 hr and then incubated in the presence or absence of thymidine or gemcitabine for 24hr.…”
Section: Figure51 Western Blot Analysis Of Atm Activation In Htert-mentioning
confidence: 99%
“…The following agents were used to potentially abrogate bystander signalling pathways inducing gH2AX foci in nontargeted cells: 1% DMSO as a ROS scavenger, 0.5 mg/ml Filipin for abrogation of signalling through glycosphingolipidenriched membrane microdomains or lipid rafts, 10 mg/ml anti-TGF-beta 1 (all Sigma, Poole, UK), 5 mM ATM inhibitor KU-55933 (Hickson et al, 2004) and 5 mM DNA-PK inhibitor NU 7026 (Veuger et al, 2003) (both kindly provided by G Smith, KuDos, Cambridge, UK). Cells were incubated with the inhibitors 10 min before irradiation and the inhibitors were present during irradiation and subsequent incubation time.…”
Section: Treatment For Potential Blocking Of Bystander Signalsmentioning
confidence: 99%
“…We found that both cell types were capable of generating signals inducing gH2AX foci in bystander cells for a prolonged time up to 24-48 h after irradiation. The ATM inhibitor KU-55933 (Hickson et al, 2004) and the DNA-PK inhibitor NU 7026 (Veuger et al, 2003) could not suppress the induction of gH2AX foci in bystander cells suggesting the involvement of ATR in H2AX phosphorylation in these cells. This could be confirmed by the finding that ATR-mutated cells did not show the induction of gH2AX foci in bystander cells.…”
Section: Introductionmentioning
confidence: 99%